2019
DOI: 10.1124/dmd.119.089508
|View full text |Cite
|
Sign up to set email alerts
|

NRF2-Independent Regulation of Intestinal Constitutive Androstane Receptor by the Pro-Oxidants Cadmium and Isothiocyanate inhUGT1Mice

Abstract: Environmental toxicants such as heavy metals from contaminated water or soil and isothiocyanates (ITC) from dietary sources act as pro-oxidants by directly generating reactive oxygen species (ROS) or through depleting cellular antioxidants such as glutathione. Toxicants can alter drug metabolism, and it was reported that CYP2B10 and UGT1A1 are induced by phenethyl isothiocyanate (PEITC) through the constitutive androstane receptor (CAR). The possibility that nuclear factor erythroid 2-related factor 2 (NRF2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…The induction of intestinal UGT1A1 by OCA catalyzes the metabolism of serum bilirubin, similar for what we have shown when intestinal UGT1A1 is induced following oral administration of other agents such as cadmium (Liu et al, 2016;Paszek and Tukey, 2020), arsenic (Liu et al, 2016), isothiocyanates (Yoda et al, 2017;Paszek and Tukey, 2020), and formula (Fujiwara et al, 2012). Induction of intestinal UGT1A1 is sufficient, in the absence of any regulation of liver UGT1A1, to metabolize and clear serum bilirubin.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The induction of intestinal UGT1A1 by OCA catalyzes the metabolism of serum bilirubin, similar for what we have shown when intestinal UGT1A1 is induced following oral administration of other agents such as cadmium (Liu et al, 2016;Paszek and Tukey, 2020), arsenic (Liu et al, 2016), isothiocyanates (Yoda et al, 2017;Paszek and Tukey, 2020), and formula (Fujiwara et al, 2012). Induction of intestinal UGT1A1 is sufficient, in the absence of any regulation of liver UGT1A1, to metabolize and clear serum bilirubin.…”
Section: Discussionsupporting
confidence: 83%
“…Our laboratory previously reported that UGT1A1 can be transcriptionally induced by several nuclear receptors like PXR (Chen et al, 2012), CAR (Yoda et al, 2017;Paszek and Tukey, 2020), peroxisome proliferator-activated receptor alpha (PPARα) (Senekeo-Effenberger et al, 2007), liver X receptor alpha (LXRα) (Hansmann et al, 2020), the environmental sensors aryl hydrocarbon receptor (AhR) (Yueh et al, 2003), nuclear factor erythroid-2 related factor 2 (Nrf2) (Yueh and Tukey, 2007;Yoda et al, 2017) and following activation of the IKK/NFκB pathway (Liu et al, 2016). A recent clinical report suggested that obeticholic acid (OCA) treatment, an FXR activator, lowers serum bilirubin levels (Parés et al, 2020).…”
Section: Treatment Of Oca In Neonatal Hugt1 Micementioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that an acute testicular toxic dose of Cd (2.0 mg/kg i.p) reduced hepatic microsomal aryl hydrocarbon hydroxylase (now known as Cyp1a) and aminopyrine N-demethylase (now known as Cyp3a) activities more in male rats than in female rats in a testosterone-dependent manner 21 . In the intestine of mice, acute Cd exposure activated the xenobiotic-sensing nuclear receptor constitutive androstane receptor (CAR) and upregulated its target gene Cyp2b10 22 . However, chronic Cd exposure in drinking water has not been shown to produce a significant effect on hepatic drug metabolism (up to 200 mg/L and up to 12 weeks) 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…A CYP1A2-knockout rat model generated via a CRISPR-Cas9 approach shows no change in hepatic AHR mRNA levels but a strong compensatory increase in CYP1A1 expression (Sun et al, 2021). The induction of intestinal CYP1A1 by cadmium in UGT1humanized mice is lost in this mouse model lacking Nrf2 (Paszek and Tukey, 2020). Hepatic AHR mRNA levels and expression of AHR target genes are induced in a peroxisome proliferator-activated receptor-α (PPARα)-dependent fashion by the Olea europaea constituent oleuropein (Malliou et al, 2021).…”
mentioning
confidence: 99%